Modern Transformation in Agriculture for Onion Watering Automation with Solar Cell and IOT Technology - Isac Ilham Akbar Habibi; Septriandi Wirayoga; Miftakhul Huda; Guntur Yanuar Astono (Fakultas Teknik Universitas Bhayangkara, 2024)
Shallots are a key agricultural commodity in Indonesia, requiring careful water management for optimal growth. Excessive water can cause rot in shallot seedlings, while insufficient water leads to wilting and yellowing leaves, affecting crop quality. This research designs an IoT-based automatic monitoring and watering system to address these challenges. The system includes a soil moisture sensor, a DHT22 sensor for air temperature and humidity, an ESP32 microcontroller, a water pump, and a solar panel as its energy source, controllable via an Android application. The system maintains ideal soil moisture for each growth stage: 80-90% during germination, 60-70% for the vegetative stage, and 50-60% during the generative stage, with optimal air temperatures of 25-30°C. Real-time data from sensors are processed by the ESP32, which activates the water pump via a DC relay when soil moisture falls below the threshold. Testing shows the system operates continuously, with solar panels charging a VRLA battery daily to sustain nighttime operation. Battery voltage fluctuates between 12.5 V and 15.0 V, maintaining a charge above 12.0 V after sunset. To ensure reliability in extreme weather, the system employs waterproof enclosures for all components and uses sensors calibrated to maintain accuracy in saturated soils. An MPPT charge controller optimizes solar energy usage during low sunlight, while selected components operate in a wide temperature range, ensuring extreme heat or cold performance. This system improves water efficiency, reduces manual labor, and offers an environmentally friendly solution for shallot cultivation, particularly in remote areas without conventional power access. Its resilience to environmental challenges enhances productivity and supports sustainable agricultural practices.